Uji Aktivitas Antibakteri Sediaan Gel Hand Sanitizer Ekstrak Etanol Daun Kaktus Pakis Giwang (Euphorbia milli) Terhadap Bakteri Pseudomonas aeruginosa - Putra, I Made Agus Sunadi; Putri, Ni Putu Devi Nirmala; Santoso, Puguh (Usadha, 2025)
The Covid-19 pandemic has heightened public awareness of hand hygiene thus creating a demand for safe and effective natural-based hand sanitizers. This study aimed to determine the antibacterial activity of hand sanitizer gel containing ethanol extract of Euphorbia milli leaves against Pseudomonas aeruginosa. The extract was obtained through maceration of 500 g of powdered leaves in 70% ethanol and formulated into gels with concentrations of 5%, 10%, and 15% using CMC-Na, glycerin, propylene glycol, and methyl paraben as base ingredients. Physical quality tests included organoleptic properties, homogeneity, pH, and spreadability, while antibacterial activity was assessed using the disc diffusion method on Mueller Hinton Agar. All formulations showed brown colour, homogeneous texture, and pH averaging 5.5, meeting standard requirements. The spreadability ranged between 5.0–6.0 cm, indicating good application consistency. Inhibition zone diameters against P. aeruginosa increased with extract concentration: 6.52 ± 0.26 mm (5%), 7.51 ± 0.30 mm (10%), and 8.39 ± 0.35 mm (15%), whereas the positive control (Ciprofloxacin 5 µg) produced 29.92 ± 1.06 mm and the negative control showed 0 mm. Based on inhibition zone classification, all formulations exhibited moderate antibacterial activity. In conclusion, the ethanol extract of Euphorbia milli leaves demonstrates antibacterial potential against Pseudomonas aeruginosa, with effectiveness increasing proportionally to concentration, suggesting its potential as a natural active ingredient for hand sanitizer formulations